Study on the behavior and mechanism of methane desorption-diffusion for multi-scale coal samples under multi-temperature conditions. (15th November 2022) - Zhao, Dong; Li, Xiaowei; Feng, Zengchao; Pu, Yuxin; Chang, Haiming; Jia, Yichao
Highlights: Obvious methane release by thermal in large specimen and low pressure. More activation energy is required for methane diffusion in columnar coal. Methane diffusion from coal matrix to the fracture is enhanced by thermal action. Pressure-depleted reservoirs of CBM extraction could be improved by thermal action. Abstract: Based on the background of coalbed methane thermal mining and mine gas control, this paper mainly investigates the effect of thermal action on the enhanced methane desorption-diffusion characteristics of multi-scale coal samples under different conditions and the corresponding mechanism through a series of methane dispersion experiments and theoretical analysis. The results show that the relationship between temperature and diffusion coefficient can be described by the modified Arrhenius equation, and the activation energy required for gas diffusion in columnar coal is greater than that in granular coal; The diffusion coefficient decreases linearly with increasing adsorption pressure under non-thermal action, while the pressure-dependent diffusion coefficient variation relationship under thermal action can be described by a quadratic function; The variation law of diffusion coefficient with coal size can be explained in terms of pore distribution and effective diffusion cross-sectional area in coal. In addition, the concept of "extreme particle size" has been used to explain the significant size effect exhibited by methane desorption, and the extreme particle size of the coal sample used in this experiment is inferred to be about 1 mm. Thermal action has a significant enhanced effect on methane release in large size coal samples and at low adsorption pressure. For low-pressure reservoirs, applying appropriate thermal measures to stimulate the coal matrix can significantly promote residual methane desorption, more importantly, enhance the diffusion ability of methane from coal matrix to the fracture, increasing the matrix methane diffusion flux, which is expected to improve the capacity performance of pressure-depleted reservoirs in the middle and late stages of CBM extraction, thus achieving efficient recovery of CBM. This study has improved gas transport theory in porous media to a certain extent, and also provides a certain theoretical basis for CBM thermal mining and gas disaster prevention and control.